Optimalisasi Produksi Alat Muat Pada Pengupasan Lapisan Tanah Penutup Dengan Menggunakan Metode Overall Equipment Effectiveness (OEE) Tahun 2018 Di Blok B PT. Minemax Indonesia Kabupaten Mandi Angin Provinsi Jambi - Muhammad Rafles Yusuf; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2019)
Abstrack. Based on the production data of overburden stripping in bloc B PT.Minemex Indonesi in maret 2018, overburden stripping production did not reach the target. To find out the improvement potential of a production process and the effectiveness of using equipment, it is necessary to do an analysis using the OEE method. OEE is known as one of the applications of total productive maintenance programs that have the ability to clearly identify the root of the problem and its causal factors to make the improvement effort to be more focused. After knowing the root of the problem, multiple linear regression statistical analysis is used to determine the relationship and the maximum limits of the obstacles so that the production can be achieved. The fishbone method is then used to find more detailed of the root problems and evaluate them by referring to the results of the multiple linear regression statistical analysis that has been obtained. However, the OEE value of each excavator still <85% and has not reached the world-class OEE value> 85%, it can be concluded that the condition of the equipment is not good. It is better to do repairs to standby time and tool breakdown.Keywords: Production, Overall Equipment Effectiveness, multiple linear regression statistical analysis, Fishbone Method, Excavator